2016
DOI: 10.1055/s-0042-100228
|View full text |Cite
|
Sign up to set email alerts
|

Fähigkeit von Patienten mit einer peripheren Fazialisparese zur Erkennung von Emotionen – Eine Pilotstudie

Abstract: The present pilot study does not prove any impact on this specific patient group's ability to recognize emotions and facial laterality. For future studies the research question should be verified in a larger sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
0
6
2
Order By: Relevance
“…Our results reveal significant deficits in terms of accuracy of facial emotion recognition, in contrast with other studies that did not report any differences, e.g., [ 27 , 28 , 34 ]. This fact may be due to the large sample size (participants with facial paresis: n = 34; participants without facial paresis: n = 29) and the inclusion of different phases post-onset, with a wide range since the time of stroke (day 5 up to day 6361 post-onset).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results reveal significant deficits in terms of accuracy of facial emotion recognition, in contrast with other studies that did not report any differences, e.g., [ 27 , 28 , 34 ]. This fact may be due to the large sample size (participants with facial paresis: n = 34; participants without facial paresis: n = 29) and the inclusion of different phases post-onset, with a wide range since the time of stroke (day 5 up to day 6361 post-onset).…”
Section: Discussioncontrasting
confidence: 99%
“…This fact may be due to the large sample size (participants with facial paresis: n = 34; participants without facial paresis: n = 29) and the inclusion of different phases post-onset, with a wide range since the time of stroke (day 5 up to day 6361 post-onset). However, previous studies reported significant limitations in terms of average time taken for facial emotion recognition, e.g., [27,28], while the participants in the present study showed faster reaction times. This, in turn, could indicate that the participants after stroke replied quick and dirty [63], while they suffered from other impairments, such as deficits in attention, concentration and memory [64], in addition to the facial paresis after stroke.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations